Social Media Influencer Strategy in a Creative Digital Agency: A Case Study - Janfri Aini; Anathasia Citra (Expose: Jurnal Ilmu Komunikasi, 2019)
Creative digital agency has the responsibility to create the right communication strategy as a partner to help clients. Recently, social media influencer is one of the most eminent strategies used by agencies. By using qualitative method with case study approach and interviews with three expert informants and being highly involved in the process activities, this study aims to understand why and how a creative digital agency in Jakarta implements social media influencer strategy. The result showed that the emergence of social media influencer has shown new approaches to adjust the audience behavior, where people put more trust and tend to listen from others than advertisement. Moreover, social media influencer has provided the chance to interact directly as an effort to better engagement through two-way communication. In the process, the agency divided the team into three, which are 1) community team to find influencer and manage the administration, 2) social media team to upload any information about social media influence on brand official account, and 3) digital strategist to evaluate the strategy.